THE FUNCTIONAL CONDITION OF MICROCIRCULATION IN PATIENTS WITH GENERALIZED PERIODONTITIS ON THE BACKGROUND OF TYPE I DIABETES MELLITUS WITH CARDIOMYOPATHY - R. Y. Shkrebnyuk; O. I. Mrochko; N. R. Kluchkovska (Український стоматологічний альманах, 2018)
Diabetes mellitus is an important medical and social problem of humanity being in connection with the high prevalence and chronic course of the disease. It should be noted that according to the data by many literary sources diabetes mellitus and generalized defeats of periodontal tissues related to the pathogenesis with changes of all vascular system, in particular such as cause defeat of the blood vessels of tooth-jaw apparatus, significantly influence on the development of periodontal pathology, doing it more progressive.